The Using Pre-Questioning to Improving the Students’ Reading Comprehension Skills to the Tenth Grade Students of SMA Negeri 2 Padangsidimpuan - Siti Meutia Sari; Tinur Rahmawati Harahap; Wanro Sinaga; Elissa Evawani Tambunan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2021)
This research is mainly conducted by the writer in order to know that there is a significant effect of using the pre-questioning to improving the students’ reading comprehension skills to the tenth grade students’ of SMA Negeri 2 Padangsidimpuan or not. The number of the sample is 52 students. In this research the writer applies the cluster sampling. And as the instrument for collecting the data the writer uses the questioners for variable X and the essay test for variable Y. For getting the needed data, the writer applies the library and field research. The method of research is experiment method, that is the writes find out the different of students’ score before-after using pre-questioning method. Based on the result of research can be known the students’ mean score in pre-test is 80.76. After treatment the students’ mean score increase into 89.04. After collecting the needed the data, the next step which is done by the writer is analyzing it by using statistical analysis. The statistical formulation which is used in this research is the formulation of Pearson’s Product Moment Correlation (rxy). After analyzing the collected data, it has been got that the value of correlation (rxy), that is 0.945. By consulting this value to the table interpretation given before, it is known that this value can be categorized into the very high correlation category. It means that there is a significant effect of using the pre-questioning to improving the students’ reading comprehension skills to the tenth grade students’ of SMA Negeri 2 Padangsidimpuan. The hypothesis of this research accepted.